METHODOLOGICAL APPROACHES TO ANALYSIS OF COMPONENTS AND ASSESSMENT OF THE EFFECTIVENESS OF THE COMPANY MARKETING MANAGEMENT SYSTEM (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The marketing management system plays a crucial role in ensuring the flexibility and adaptability of an organization to market conditions, contributing to the formation of competitive advantages. To develop a company's marketing management system, it is essential to create a methodology for analyzing its components and assessing its effectiveness.The purpose of the article. The purpose of this article is to research and develop methodological approaches for analyzing the components and assessing the effectiveness of a company's marketing management system.Methods. The use of theoretical generalization, analysis, and synthesis methods allowed for the development of a proprietary methodological approach to analyzing and evaluating the effectiveness of a company's marketing management system.Results. The article presents a theoretical analysis of literature sources regarding existing methodological approaches to assessing a company's marketing management system. The stages of evaluating the effectiveness of a company's marketing management system have been identified. The article groups the criteria that enable conclusions to be drawn regarding the analysis of the system’s components, including criteria for analyzing the components of a company's marketing management system based on elements of the marketing mix: product policy management, pricing management, distribution policy management, and communication policy management. Additionally, criteria for assessing the effectiveness of a company's marketing management system are proposed.Conclusions. The proposed methodological approach to analyzing the components and assessing the effectiveness of the marketing management system includes an analysis of management functions, elements of the marketing mix, and key performance indicators.
Keywords: marketing management system, components of the marketing management system, criteria for analyzing the components of the marketing management system, criteria for assessing the effectiveness of the marketing management system.